The Implementation of Project-Based Learning to Improve the Learning Interest and Student Achievement - Fauzia, Hamida; Prastiti, Sawitri Dwi (Universitas Negeri Malang, 2017)
The purpose of the research is project based learning model to improve student interest and achademic achievment of second grade of Social departement of State Senior High School 3 Blitar Through the implementation of project-based learning model. The research design is a Classroom Action Research (CAR) also using achademic achievment test and observation instruments. The research shows that the students learning interest and achademic achievment can be improved.Keywords: Project-Based Learning Model, Learning Interest, Achademic Achievment